An Analysis of Green Environment Alerting Bot - B.Kiran Bala1, K.Premitha2, D.Shiporal Shiny3, S.Priyadharshini4, S.Reetha Dhevi 5 (International Journal of Advanced Science and Technology, 2020)
The present environment pollution is very high in all over the world and to support the society and peoplefor live update and safety purpose. This analysis is mainly used to find out the humidity inside the roomas well as outside the room, heat and temperature of the room it is very important feature of this systemand it will act as a fire alter and gas leakage in the room can also be separated and identify from theroom in the environment by alerting the users is the main objective of this system and for that process thissystem is used bot technology with the help of raspberry pi technology and users come to know thesudden change in present environment through beep so that users can be alter and take precaution stepsto make safe themselves and the society.